The .U.S Intervention in Afghanistan: The Critical Approach of Peace Building (2001-2021) - Tahr,i Salma; Nebeg ,Raouf (Faculty of Letters and Foreign Languages Department of English, 2023)
This research examines the U.S intervention in Afghanistan After the 9/11 event to 2021.It also discusses the U.S efforts, goals and plans during the two decades. The purpose of this work is to shed light on the U.S Strategy in Afghanistan and explain the reason behind this war that took a long time. In order to reach this purpose, the research relied on books articles sites analyzing author's saying, speeches and quotes. On the one hand, the intervention in Afghanistan was the war on terror and the start to rebuild Afghanistan. On the other hand, after 20 years the American forces retreated empty-handed, losing both materially and humanly. It lost its longest struggle in history to the Taliban despite the might of America and its Allies